Countering Religious Extremism: Innovative Deradicalization Strategies For Building Inclusive Communities - Sirojuddin Abror; Bambang Wahrudin (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Religious extremism poses significant threats to global peace, social cohesion, and inclusive development, requiring innovative and comprehensive deradicalization strategies. This study explores contemporary approaches to countering religious extremism by integrating preventive, rehabilitative, and inclusive frameworks. Using a qualitative descriptive-analytical method, data were collected from academic literature, government reports, policy documents, and successful case studies in multiple contexts, including Indonesia, Malaysia, and international initiatives. The findings highlight four innovative strategies: (1) educational curriculum reforms that promote critical thinking, pluralism, and tolerance; (2) digital literacy campaigns to counter extremist narratives and empower youth against online radicalization; (3) interfaith dialogues and community engagement to foster empathy, trust, and collaboration; and (4) rehabilitation and reintegration programs combining psychological counseling, religious moderation, and vocational training. The study emphasizes the necessity of multisector collaboration among governments, educational institutions, civil society, and international organizations to build inclusive and resilient communities. By adopting a holistic and participatory approach, societies can mitigate the root causes of radicalization, enhance intergroup harmony, and strengthen collective resistance to violent ideologies. These findings provide valuable insights for policymakers, educators, and community leaders seeking to design effective counter-extremism strategies tailored to diverse sociocultural contexts.